Turisti a Lampedusa. Note sul nesso tra mobilità e patrimonio nel Mediterraneo - Francesco Vietti (Archivio Antropologico Mediterraneo)
Mobility studies can provide a fruitful approach to understand the relationship between migration and tourism in many Mediterranean contexts. Some islands that rely on tourism for their economic survival have in recent years become a place of transit and reception of significant migration flows. This contribution focuses on the case of Lampedusa, through an ethnographic research aimed at investigating the role played by mobility in the subsequent historical periods of social, cultural and economic transformation of the island. By studying the processes of heritage-making underway, with particular reference to the local cult of Our Lady of Porto Salvo, the aim is to highlight the ways in which migrations have been integrated into the cultural heritage of Lampedusa and have become a constitutive part of its tourist image.